Between “the Culture of the Olive Tree” and “the Lexus Culture”: Types of Spirituality in E-greetings - Brzozowska-Krajka, Anna (Literatura Ludowa. Journal of Folklore and Popular Culture, 2020)
This study concerns the relationship of neofolklore/cyberfolklore to religion in the globalized world and some issues fundamental for contemporary evaluation of religious phenomena, such as types/models of spirituality and their co-existence, forms of their expression as manifest in electronic communication (interface to interface) and the genre of e-greetings. These types may be placed on three levels: 1. religious spirituality (the culture of traditional values – “the culture of the olive tree”), 2. the spirituality of those who believe in a different way (private religion), and 3. secular spirituality (a play with tradition – the ideology of consumerism, the “Lexus culture”). This anthropological analysis of e-greetings is focused on the essence of holy/festive time pertaining to Christ’s Resurrection (the most important Catholic feast) and Easter e-greetings. However, these types of spirituality are paradigmatic for other phases in the liturgical year (especially Christmas and New Year rituals). The constantly growing collections of such e-greetings refer to the “festive alphabet” and indicate an increasing tendency for secularization in experiencing important dates of the liturgical calendar, which in turn reduces their sacred essence.